2006
DOI: 10.4049/jimmunol.176.9.5438
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of T Cell Activation via CD4 Dimers

Abstract: The onset of activation in Th cells is triggered by localized coengagement of TCRs and the coreceptor CD4. A CD4 crystal suggested that CD4 may form dimers in some circumstances. In this study, we use live-cell fluorescence resonance energy transfer imaging to demonstrate that CD4 dimers are present at a basal level on the cell surface and accumulate at the synapse. Mechanistically, we reveal two conditions under which dimers are highly relevant. First, CD4 dimers are more proficient in mediating prolonged cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 56 publications
0
23
1
Order By: Relevance
“…Silencing of CD4 resulted in the expected impairment of antigen-dependent T-cell activation [13][14][15]. siRNA-mediated knockdown of the Th2 transcription factor GATA-3 abolished the expression of its target genes, the prototypic Th2 cytokines IL-4 and IL-5, as reported for GATA-3 knockout mice [17,18].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Silencing of CD4 resulted in the expected impairment of antigen-dependent T-cell activation [13][14][15]. siRNA-mediated knockdown of the Th2 transcription factor GATA-3 abolished the expression of its target genes, the prototypic Th2 cytokines IL-4 and IL-5, as reported for GATA-3 knockout mice [17,18].…”
Section: Discussionmentioning
confidence: 88%
“…Since the CD4 molecule is an important co-stimulator [13][14][15], we analyzed the effect of CD4 knockdown in primary T cells upon antigen-dependent activation in vitro and in vivo. TCR-transgenic (OVA-Tg) CD4 1 T cells were labeled with CFSE and transfected with 1000 pmol of stabilized or conventional CD4 siRNA, stabilized control siRNA (siGFP) or nucleofected but without siRNA.…”
Section: Sirna-transfected T Cells Remain Functional and Maintain Knomentioning
confidence: 99%
“…In human CD4, K 318 and Q 344 were identified as important residues for a non-covalent dimer association between D4 of adjacent CD4 molecules [38], and it has been speculated that this aligning of two CD4 monomers gives the opportunity for efficient forming of a covalently disulfide linked CD4 dimers [37]. has been demonstrated that CD4 dimerization is required for CD4-mediated T-cell activation [38,39], and it has been indicated that the preferred MHC class II co-receptor is disulfide linked dimeric CD4 [37]. Also, the connecting peptide region of the two-domain CD4-like molecules can be important for MHC binding, as a high percentage of prolines (about 21% in halibut CD4-2) may allow an extended structure so that the D1 of CD4-2 can reach the MHC molecule.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 JRFL Env-eYFP expressor was generated by inserting the codonoptimized sequence of HIV-1 JRFL Env (residues 1 to 711) at the N terminus of enhanced yellow fluorescent protein (eYFP) (from BD Clontech). The CD4-eCFP fusion protein was previously described (38). Transmitted/founder (T/F) envelope expressors from clades C (C1086) (39)(40)(41) and D (190049) were previously described (42), HIV-2 7312A (43, 44) and SIV (45) envelope expressors were previously described.…”
Section: Methodsmentioning
confidence: 99%